2020
DOI: 10.1371/journal.pone.0222619
|View full text |Cite
|
Sign up to set email alerts
|

Conditional KCa3.1-transgene induction in murine skin produces pruritic eczematous dermatitis with severe epidermal hyperplasia and hyperkeratosis

Abstract: Ion channels have recently attracted attention as potential mediators of skin disease. Here, we explored the consequences of genetically encoded induction of the cell volume-regulating Ca 2+ -activated KCa3.1 channel (Kcnn4) for murine epidermal homeostasis. Doxycycline-treated mice harboring the KCa3.1+-transgene under the control of the reverse tetracycline-sensitive transactivator (rtTA) showed 800-fold channel overexpression above basal levels in the skin and solid KCa3.1-currents in keratinocytes. This ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Our group, as well as others, have demonstrated that mice in which protease activated receptor 2 is overexpressed in keratinocytes develop hypersensitivity to pruritogens and house dust mites (Frateschi et al 2011;Braz et al 2021). Constitutive expression of Ca++ activated KCa3.1 channel in keratinocytes also leads to intense pruritus and skin lesions (Lozano-Gerona et al 2020). And under inflammatory and dry skin contexts, keratinocytes can release cytokines, including thymic stromal lymphopoietin (TSLP) and IL-33, which can directly activate sensory nerves to trigger pruritus (Wilson et al 2013;Trier et al 2022;Liu et al 2016).…”
Section: Keratinocyte-derived Mechanisms That Produce Itchmentioning
confidence: 90%
“…Our group, as well as others, have demonstrated that mice in which protease activated receptor 2 is overexpressed in keratinocytes develop hypersensitivity to pruritogens and house dust mites (Frateschi et al 2011;Braz et al 2021). Constitutive expression of Ca++ activated KCa3.1 channel in keratinocytes also leads to intense pruritus and skin lesions (Lozano-Gerona et al 2020). And under inflammatory and dry skin contexts, keratinocytes can release cytokines, including thymic stromal lymphopoietin (TSLP) and IL-33, which can directly activate sensory nerves to trigger pruritus (Wilson et al 2013;Trier et al 2022;Liu et al 2016).…”
Section: Keratinocyte-derived Mechanisms That Produce Itchmentioning
confidence: 90%
“…Treatment with the KCa3.1-selective blocker Senicapoc significantly suppressed spongiosis and hyperplasia, as well as the induction of IL-1β and IL-6. That study thus identified KCa3.1 as a regulator of epidermal homeostasis and spongiosis and a potential therapeutic target for eczematous dermatitis [ 21 ]. The signaling pathways of ion channels in immune cells are summarized in Figure 3 .…”
Section: Ion Channels In Immune Cellsmentioning
confidence: 99%
“…nAChR α5 ↑ in keratinocytes [11] α7 ↑ in keratinocytes [4] ↑ in immune cells [23] TRPA1 ↑ in keratinocytes [26] TRPV1 ↑ in keratinocytes [14] no change in keratinocytes [26] ↑ in immune cells [27] TRPV3 ↑ in keratinocytes [28] ↓ in immune cells [27] R416Q, R416W, L655P, W692S, L694P, G568D, G568V, L673F: ion channel activity ↑ severe Olmsted syndrome (L673F, W692S) mild Olmsted syndrome variants (R416Q) [29] G573A [30] TRPV4 ↑ in keratinocytes [31] ↓ in immune cells [27] ↑ in neurons [32] TRPM TRPM2 ↑ TRPM4, M7 ↓ in immune cells [27] TRPM8 ↓ in neurons [32] I1033M, I1040T (human): ion channel activity ↑ [33] I1029M (mouse): ion channel activity ↑ [34] TRPC TRPC1,3,4,5,6,7 ↓ in keratinocytes [35] TRPC6 ↓ in immune cells [27] CaSR ↓ in epidermis [36] STIM/ORAI ↓ in epidermis [36] ANO1 ↑ in keratinocytes [9] Nav Nav1.8 ↑ in keratinocytes [37] Polycystin PC1 ↓ in keratinocytes [38] Kv Kv1.3 ↑ in epidermis [39,40] KCa Kca3.1 ↑ in epidermis [21]…”
Section: Type Of Ion Channels Expression Change In Psoriasis Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, it has been increasingly recognized as a promising drug that can be repurposed for clinical use. In an effort to repurpose senicapoc, it has been tested in Alzheimer's disease [48], pulmonary fibrosis [25], skin disease [49], acute respiratory distress syndrome [50], and most recently in COVID-19 patients with severe respiratory insufficiency [51]. The increasing interest in senicapoc has led to the development of self-nanoemulsifying drug delivery systems to improve the aqueous solubility and cell permeation of senicapoc [52].…”
Section: Kca31 In Diabetic Kidney Diseasementioning
confidence: 99%